Web Therapy for Internet Addicts: A Case Study of Self-Healing by Social Media Addicts in Indonesia - KURNIASIH, NUNING; Amriwijaya, Julian (Record and Library Journal, 2018)
This study aims to analyze how the information sources on the internet used as therapy treatment (Web Therapy) by internet addicts, especially social media addicts. The method used is qualitative method based on case study perspective. The method used to collect data incorporates in-depth interview, observation, and literature study. The informants are seven internet addicts who acknowledge themselves as internet addicts, especially social media addicts not by medical diagnostic as one and been using internet sources as a treatment to overcome their mental issue. Triangulation is conducted by interviewing a psychology expert. The study results show that (1) The informants admit that information sources on the internet help them reduce stress while under pressure. (2) The informants admitted the initiative comes within themselves to use information sources on the internet in order to reduce stress. (3) There are some ways for informants to identify their personal problems, that is (a) When they feel like they have no one around to talk with, to share their problems with, they use chatting platform to talk with and positive feedbacks from social media. (b) When they encounter negative psychological condition, they need entertainment from internet sources to be relaxed and refresh. (c) When they need contemplation they will look up for some information sources on the internet which might help them to contemplate. (4) To employ self-healing using Web Therapy, the informants choose (a) Entertaining information sources that can help them laugh and relax (b) Information sources contain references on how to cope with their problems. (c) Information sources that can help them to contemplate when encounter problems. (d) Interactive information sources where they can interact and communicate with friends online. (5) The informants prefer social media such as online games with multiple players, youtube, facebook, online forums longue such as kaskus.com and detik.com, and the form of information including games, movies, music, articles on health, food, humor series, chatting, memes, sarcasms, and satyrs (6) The informants agree that although they feel better after using some information sources on the internet as a treatment for self-healing therapy, but it is only temporary not a permanent one. They are also aware of the significant to face their own problems and cope with it. This study results can be the groundwork for libraries to develop Web Therapy services.